Asuhan Keperawatan Gerontik Pada Pasien Dengan Gouth Arthritis Di Wisma Delima Panti Sosial Tresna Werdha Kasih Sayang Ibu Batusangkar - Assyfa Ashil; Hasmita .; Sandra Dewi; Armaita . (CV. ITTC INDONESIA, 2026)
Based on data from the World Health Organization (WHO), the prevalence of gout arthritis among the elderly has increased globally, with an incidence rate of approximately 3–6%. Gout arthritis is an inflammatory joint disease caused by the accumulation of uric acid crystals, characterized by pain, swelling, and limited mobility. This study aims to describe gerontic nursing care in patients with gout arthritis at PSTW Kasih Sayang Ibu Batusangkar.The method used is a case study with a nursing process approach including assessment, diagnosis, intervention, implementation, and evaluation. The assessment results in Mrs. A showed complaints of joint pain, limited mobility, and sleep disturbances. The nursing diagnoses established were chronic pain, impaired physical mobility, and sleep pattern disturbance.The interventions provided included pain management, mobilization exercises, and health education. Implementation was carried out through warm compresses, light exercises, and education on a low-purine diet. The evaluation showed a decrease in pain intensity, improvement in mobility, and better sleep patterns.In conclusion, comprehensive gerontic nursing care is effective in overcoming problems in patients with gout arthritis. It is recommended that healthcare providers enhance education and continuous care to improve the quality of life of the elderly.